2011
DOI: 10.1371/journal.pone.0017144
|View full text |Cite
|
Sign up to set email alerts
|

Close Encounters in a Pediatric Ward: Measuring Face-to-Face Proximity and Mixing Patterns with Wearable Sensors

Abstract: BackgroundNosocomial infections place a substantial burden on health care systems and represent one of the major issues in current public health, requiring notable efforts for its prevention. Understanding the dynamics of infection transmission in a hospital setting is essential for tailoring interventions and predicting the spread among individuals. Mathematical models need to be informed with accurate data on contacts among individuals.Methods and FindingsWe used wearable active Radio-Frequency Identificatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
245
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(259 citation statements)
references
References 31 publications
(43 reference statements)
13
245
1
Order By: Relevance
“…Here, the pioneering study was the Reality Mining project, where students of Massachusetts Institute of Technology were equipped with cell phones whose Bluetooth devices could detect their proximity to others [37]. The SocioPatterns project has developed a platform that allows physical proximity measurements based on wearable badges equipped with radiofrequency identification devices (RFID) [24]; these devices have been utilized in measurements of dynamic and temporal proximity networks of patients [63], school children [142], and conference attendees [140]. Because the human body acts as a shield for the proximity-sensing RF signals, such sensors only record contacts when the individuals are facing each other, and thus a contact can also be considered as indicative of communication between the individuals [24,64,121,141].…”
Section: Physical Proximitymentioning
confidence: 99%
“…Here, the pioneering study was the Reality Mining project, where students of Massachusetts Institute of Technology were equipped with cell phones whose Bluetooth devices could detect their proximity to others [37]. The SocioPatterns project has developed a platform that allows physical proximity measurements based on wearable badges equipped with radiofrequency identification devices (RFID) [24]; these devices have been utilized in measurements of dynamic and temporal proximity networks of patients [63], school children [142], and conference attendees [140]. Because the human body acts as a shield for the proximity-sensing RF signals, such sensors only record contacts when the individuals are facing each other, and thus a contact can also be considered as indicative of communication between the individuals [24,64,121,141].…”
Section: Physical Proximitymentioning
confidence: 99%
“…They analyze, for example, their activity in social web platforms like Facebook, Twitter and other social media together with status and their research seniority. These experiments have also extended their focus from conferences to schools [10] and hospitals [11].…”
Section: Related Workmentioning
confidence: 99%
“…The interval between successive conversation events for an individual or a given pair of individuals often follows a power law [1,[4][5][6]8,[17][18][19][20]. Modeling studies have revealed implications of these empirical results in contagions [4,6,9,[21][22][23][24][25] and opinion formation [26,27]. In contrast to conventional models in which the Poisson interval distribution is assumed, these results indicate that the next conversation time, given the previous one, is relatively predictable in that a conversation event in the recent past is a precursor to a burst of events in the near future.…”
Section: Introductionmentioning
confidence: 99%